Original articleFaulty position of cerebellar cortical neurons as a sequel of disturbed neuronal migration - Laure-Kamionowska, Milena; Taraszewska, Anna; Maślińska, Danuta; Raczkowska, Barbara (Folia Neuropathologica, 2006)
The object of our report is the presentation of the morphological picture of cerebellar cortex malformation as a sequel of disturbed neuronal migration. In the disarranged tissue, cavities with a network of meningeal tissue and embedded pathological vessels were noted. The external granule cells did not form a proper external granule layer, but moved deeper, forming irregular aggregates. Abnormally aggregated external granular cells invaded the cerebellar tissue. Abnormal Purkinje cell positioning and a disarranged molecular layer were observed. The normal layered pattern of the cerebellar cortex was disorganized. The presented cases represent a spectrum of morphological changes which are the consequence of aberrant migration. Against a background of vascular pathology affecting the meningoglial network the migration pathways were disrupted. The defective movement of neurons and their faulty maturation resulted in disturbances of cortical layering, and defects of cerebellar folia formation.